ICTV Virus Taxonomy Profile: Ophioviridae - Garcia, Maria Laura (2017)
The Ophioviridae is a family of filamentous plant viruses, with single-stranded negative, and possibly ambisense, RNA genomes of 11.3-12.5 kb divided into 3-4 segments, each encapsidated separately. Virions are naked filamentous nucleocapsids, forming kinked circles of at least two different contour lengths. The sole genus, Ophiovirus, includes seven species. Four ophioviruses are soil-transmitted and their natural hosts include trees, shrubs, vegetables and bulbous or corm-forming ornamentals, both monocots and dicots. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the taxonomy of the Ophioviridae, which is available at http://www.ictv.global/report/ophioviridae.